Analisis Kondisi Fisik Atlet Unesa Women Football Club meliputi Daya Tahan, Kecepatan, Kelincahan, Kekuatan, dan Daya Ledak - Wina Arlina Putri Andini; Achmad Widodo; Indra Himawan Susanto; Mokhamad Nur Bawono (Lembaga Pengembangan Kinerja Dosen, 2024)
Athletic physical condition is a key factor in determining an athlete's performance during competitions. This study aims to assess the physical condition of Unesa Women FC athletes using a descriptive quantitative method, involving 20 athletes as the sample. Data was collected through a series of physical tests to measure various aspects of physical fitness, including aerobic endurance, speed, agility, leg strength, and explosive power. The tests conducted included the Multistage Fitness Test (MFT) for aerobic endurance, a 30-meter sprint for speed, Illinois Agility Run for agility, Leg Dynamometer for leg strength, and Jump MD for explosive power. The results of the study show that the average VO2Max of the athletes is 30.8 ml/kg/min, which falls into the